Analisis Efektivitas Tata Kelola TI Menggunakan Framework Framework Cobit 5 pada PT Bima Mandira Abadi - Agung Yuliyanto Nugroho (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This study aims to analyze the effectiveness of implementing the COBIT 5 framework in Information Technology (IT) governance in organizations. The main focus is to evaluate the extent to which COBIT 5 is able to improve IT management, operational efficiency, and the achievement of the organization's strategic objectives. This study uses a case study approach with qualitative methods. Data were collected through interviews with IT stakeholders, analysis of IT policy and procedure documents, and employee surveys to assess their perceptions of the effectiveness of IT governance. The assessment was carried out by comparing the implementation of COBIT 5 against the performance indicators and controls set out in the framework. This study revealed that although COBIT 5 provides a comprehensive framework for IT governance, the success of its implementation is highly dependent on managerial support, adequate training, and adjustments to the specific needs of the organization. Recommendations for improving effectiveness include strengthening training, improving internal communication, and periodic evaluation of COBIT 5 implementation. The implementation of COBIT 5 has shown substantial benefits in improving IT governance and supporting the achievement of organizational goals. However, to maximize its effectiveness, attention is needed to the aspects that influence the adoption and implementation of this framework.